2017
DOI: 10.1038/bjc.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cdk5 induces cell death of tumor-initiating cells

Abstract: Background:Tumour-initiating cells (TICs) account for chemoresistance, tumour recurrence and metastasis, and therefore represent a major problem in tumour therapy. However, strategies to address TICs are limited. Recent studies indicate Cdk5 as a promising target for anti-cancer therapy and Cdk5 has recently been associated with epithelial–mesenchymal transition (EMT). However, a role of Cdk5 in TICs has not been described yet.Methods:Expression of Cdk5 in human cancer tissue was analysed by staining of a huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Although CDK5 shares homologous structure with other CDKs, it is not cyclin-dependent and does not need to be phosphorylated in the T-loop for activation (66). CDK5 expression is upregulated in several types of cancer, and inhibition induces cancer cell death through a FOXO1-Bim pathway or mitochondrial dysfunction (67)(68)(69)(70)(71)(72)(73). Ehrlich et al (74) showed that expression of CDK5 was increased in HCC tissues, and was correlated with malignant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Although CDK5 shares homologous structure with other CDKs, it is not cyclin-dependent and does not need to be phosphorylated in the T-loop for activation (66). CDK5 expression is upregulated in several types of cancer, and inhibition induces cancer cell death through a FOXO1-Bim pathway or mitochondrial dysfunction (67)(68)(69)(70)(71)(72)(73). Ehrlich et al (74) showed that expression of CDK5 was increased in HCC tissues, and was correlated with malignant phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that CDK5 may function as a tumor activator in lung cancer. CDK5 has been reported up-regulated and to act as a tumor activator in many human cancers, including colorectal cancer 43 , breast cancer 44 , pancreatic cancer 45 . These results showed that CDK5 can be a promising anticancer target.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor‐initiating cells (TIC) account for chemoresistance, tumor recurrence and metastasis and therefore represent a major problem in tumor therapy. Cyclin‐dependent kinase (Cdk5) inhibition induces apoptosis of tumors by stabilizing the transcription factor FOXO1, which is correlated with increased levels of the proapoptosis protein, Bim . Exogenous IGF‐1R promotes the expression of FOXO1 and insulin‐like growth factor binding protein‐1 (IGFBP‐1), evidenced by suppression of breast cancer, whereas IGF‐1R knockdown decreases FOXO1 protein levels and promotes the proliferation of MCF‐7 cells .…”
Section: Roles Of Foxo1 In Diverse Human Neoplasmsmentioning
confidence: 99%
“…Cyclin-dependent kinase (Cdk5) inhibition induces apoptosis of tumors by stabilizing the transcription factor FOXO1, which is correlated with increased levels of the proapoptosis protein, Bim. 81 Exogenous IGF-1R promotes the expression of FOXO1 and insulin-like growth factor binding protein-1 (IGFBP-1), evidenced by suppression of breast cancer, whereas IGF-1R knockdown decreases FOXO1 protein levels and promotes the proliferation of MCF-7 cells. 82 Moreover, some other studies have demonstrated that FOXO1 can exert antitumor actions in breast cancer, while a detailed description is beyond the scope of this article.…”
Section: Breast Cancermentioning
confidence: 99%